German Expressionist Prints and Drawings : The Robert Gore Rifkind Center for German Expressionist Studies - volume 1 - Barron, Stephanie; Dube, Wolf-Dieter; Dückers, Alexander; Guenther, Peter; Washton Long, Rose-Carol; Raabe, Paul; Gore Rifkind, Robert; Rigby, Ida Katherine (Los Angeles : Los Angeles County Museum of Art, 1989)
Kokoschka, Oskar ; Kirchner, Ernst Ludwig ; Dix, Otto ; Schrimpf, Georg ; Heckel, Erich ; Lange, Otto ; Grosz, George ; Meidner, Ludwig ; Felixmüller, Conrad ; etc.
German Expressionist Prints and Drawings, Los Angeles County Museum of Art, Los Angeles, 1989
boek